Wear-resistant melamine impregnated paper and preparation method thereof
A three-dimensional network structure formed by cross-linking melamine urea-formaldehyde resin, organic phosphonic acid, and nano-alumina in melamine impregnated paper addresses the brittleness and wear resistance issues, achieving enhanced toughness and flame retardancy.
Patent Information
- Application Number
- CN202411312988.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
Existing melamine impregnated papers using melamine urea-formaldehyde resin are brittle and lack wear resistance.
A three-dimensional network structure is formed by cross-linking and curing melamine urea-formaldehyde resin with organic phosphonic acid, imine, and nano-alumina to create a wear-resistant melamine impregnated paper.
The resulting paper exhibits excellent wear resistance and flame retardancy due to intermolecular hydrogen bonds, ion complexation, and chelation between imine and organic phosphonic acid, along with uniform dispersion of nano-alumina, enhancing toughness and tensile strength.
Smart Images

Figure CN119177583A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of impregnated paper, in particular to wear-resistant melamine impregnated paper and a preparation method thereof. Background Art
[0002] The full name of impregnated paper is impregnated film paper. Its preparation method is to use decorative base paper as the impregnation substrate, first impregnate the impregnated substrate in amino resin, and then heat the amino resin impregnated in the impregnated substrate to solidify to form a film to obtain impregnated paper. The impregnated paper can be directly covered on the surface of the artificial board, and then firmly bonded to the surface of the board by hot pressing to form a protective film. Impregnated paper gives the board various surface properties, such as decorative, protective and flame retardant.
[0003] Melamine urea-formaldehyde (MUF) resin is a commonly used impregnating material. This thermosetting aqueous solution is composed of low-molecular condensation resins, which can penetrate the entire base paper and then form a transparent film during the thermal curing process. Due to the many advantages of MUF resin, such as high hardness, good thermal stability, and the ability to form a smooth surface, it is widely used in the manufacture of impregnated paper. For example, Chinese patent CN 202110263453.3 discloses a flame-retardant impregnated paper and a preparation method thereof, which appropriately improves the flame retardancy of the impregnated paper by utilizing MUF resin. However, the glue layer after curing of MUF resin is often brittle and easy to crack. The impregnated paper prepared using melamine urea-formaldehyde resin has poor surface wear resistance.
[0004] Therefore, how to obtain wear-resistant melamine impregnated paper is a technical problem to be solved urgently in this field. Summary of the invention
[0005] The object of the present invention is to provide a wear-resistant melamine impregnated paper and a preparation method thereof. The melamine impregnated paper provided by the present invention has excellent wear resistance and flame retardancy.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a wear-resistant melamine impregnated paper, comprising base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing of melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-alumina.
[0008] Preferably, the organic phosphonic acid comprises one or more of phytic acid, citric acid and tannic acid.
[0009] Preferably, the imine comprises one or more of polyethyleneimine, polydiethylenetriamine and chitosan.
[0010] Preferably, the nano-alumina includes one or more of α-alumina, β-alumina and γ-alumina.
[0011] Preferably, the mass ratio of the melamine urea-formaldehyde resin, the organic phosphonic acid, the imine and the aluminum oxide is 1:10:(0.1-0.2):(1-3):(1.1-3.3).
[0012] The present invention also provides a method for preparing the wear-resistant melamine impregnated paper according to the above technical solution, comprising the following steps:
[0013] (1) mixing imine with melamine urea-formaldehyde resin and performing Mannich reaction to obtain a first modified resin;
[0014] (2) mixing the first modified resin obtained in step (1) with an organic phosphonic acid to carry out a complex reaction to obtain a second modified resin;
[0015] (3) mixing the second modified resin obtained in step (2) with nano-alumina to obtain an impregnated material;
[0016] (4) The base paper is immersed in the impregnating material obtained in step (3), taken out, and cross-linked and cured to obtain wear-resistant melamine impregnated paper.
[0017] Preferably, the temperature of the Mannich reaction in step (1) is 25 to 30° C., and the time of the Mannich reaction is 10 to 15 minutes.
[0018] Preferably, the temperature of the complexation reaction in step (2) is 25 to 30° C., and the time of the complexation reaction is 30 to 35 minutes.
[0019] Preferably, the immersion time in step (4) is 1 to 2 minutes.
[0020] Preferably, the temperature of cross-linking and curing in step (4) is 120-125° C., and the time of cross-linking and curing is 1-2 min.
[0021] The present invention provides a wear-resistant melamine impregnated paper, which includes base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-alumina. The resin film in the wear-resistant melamine impregnated paper provided by the present invention is a three-dimensional network structure formed by cross-linking and curing melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-alumina; wherein the imine is grafted onto the melamine urea-formaldehyde resin, and there is an intermolecular hydrogen bond and ion complexation between the imine and the organic phosphonic acid, and the viscous agglomerate generated by the reaction of the two effectively improves the toughness of the impregnated paper; due to the rich flame-retardant nitrogen and phosphorus elements in the imine-phytic acid polyelectrolyte, it plays a positive role in the flame retardancy of the impregnated paper; in addition, there is a strong chelation between the nano-alumina and the organic phosphonic acid molecules, which are evenly dispersed in the melamine urea-formaldehyde resin to improve the tensile strength and wear resistance of the impregnated paper. The results of the examples show that the wear-resistant melamine impregnated paper provided by the present invention has a limiting oxygen index of 40.0%, a tensile strength of 69.19 MPa, an abrasion value of 14.1 mg / 100 r, and has excellent flame retardancy, toughness and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a diagram of the synthesis mechanism of the prepreg in the wear-resistant melamine impregnated paper according to an embodiment of the present invention;
[0023] Figure 2 FTIR graphs of different modified resins of the present invention;
[0024] Figure 3 : XPS graphs of different modified resins of the present invention;
[0025] Figure 4 This is a high-resolution spectrum of the MUF / PEI-PA@Nano-Al2O3 resin of the present invention. DETAILED DESCRIPTION
[0026] The invention provides a wear-resistant melamine impregnated paper, comprising base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing of melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-alumina.
[0027] The wear-resistant melamine impregnated paper provided by the present invention comprises base paper. The present invention has no special limitation on the source, size and type of the base paper, and conventional commercial products in the art can be used and selected according to the required size. In the embodiment of the present invention, the length and width of the base paper are independently 15 cm.
[0028] The wear-resistant melamine impregnated paper provided by the present invention comprises a resin film impregnated on the base paper.
[0029] In the present invention, the resin film is a three-dimensional network structure formed by cross-linking and curing of melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-aluminum oxide.
[0030] The present invention has no special limitation on the source of the melamine urea formaldehyde resin, and any commercially available product in the art can be used. In the present invention, the source of the melamine urea formaldehyde resin is preferably Linyi Jiangyuan Decoration Materials Co., Ltd.
[0031] In the present invention, the organic phosphonic acid preferably includes one or more of phytic acid, citric acid and tannic acid, and more preferably phytic acid. The organic phosphonic acid used in the present invention has a phosphoric acid group and can form a polyelectrolyte complex with imine, thereby improving the flame retardancy of the impregnated paper.
[0032] In the present invention, the imine preferably includes one or more of polyethyleneimine, polydiethylenetriamine and chitosan, and more preferably polyethyleneimine. The present invention utilizes that imine can be grafted onto melamine urea-formaldehyde resin, and there are intermolecular hydrogen bonds and ion complexation between imine and organic phosphonic acid, and the viscous coagulant generated by the reaction of the two can impregnate the toughness of paper. In the present invention, the molecular weight of the polyethyleneimine is preferably 300 to 1200, and more preferably 600. When the present invention uses polyethyleneimine with the above molecular weight, it is more conducive to the full progress of the grafting reaction.
[0033] In the present invention, the nano-alumina preferably includes one or more of α-alumina, β-alumina and γ-alumina, and more preferably γ-alumina. The present invention uses nano-alumina as a wear-resistant filler, and the surface of the nano-alumina has hydroxyl groups and residual charges. The presence of these hydroxyl groups makes the surface of the nano-alumina reactive, and there is a chelating effect between the nano-alumina and the organic phosphoric acid. The nano-alumina can be dispersed in melamine urea-formaldehyde resin to improve the tensile strength and wear resistance of the impregnated paper.
[0034] In the present invention, the particle size of the nano-alumina is preferably ≤50nm, more preferably 10-20nm. The present invention controls the particle size of the nano-alumina within the above range, has a larger specific surface area, is more conducive to fully chelating with organic phosphonic acid, and improves the wear resistance and toughness of the impregnated paper.
[0035] In the present invention, the mass ratio of the melamine urea-formaldehyde resin, the organic phosphonic acid, the imine and the aluminum oxide is preferably 110:(0.1-0.2):(1-3):(1.1-3.3), and more preferably 110:0.2:1:3.3. The present invention controls each component within the above range, which is more conducive to allowing each component to fully participate in the crosslinking and curing reaction.
[0036] In the wear-resistant melamine impregnated paper provided by the present invention, imine is grafted onto melamine urea-formaldehyde resin, and there are intermolecular hydrogen bonds and ion complexation between imine and organic phosphonic acid. The viscous agglomerates generated by the reaction of the two effectively improve the toughness of the impregnated paper; since there are rich flame-retardant nitrogen and phosphorus elements in the imine-phytic acid polyelectrolyte, it plays a positive role in the flame retardancy of the impregnated paper; in addition, there is a strong chelating effect between nano-alumina and organic phosphonic acid molecules, and it is uniformly dispersed in the melamine urea-formaldehyde resin, thereby improving the tensile strength and wear resistance of the impregnated paper.
[0037] The present invention also provides a method for preparing the wear-resistant melamine impregnated paper according to the above technical solution, comprising the following steps:
[0038] (1) mixing imine with melamine urea-formaldehyde resin and performing Mannich reaction to obtain a first modified resin;
[0039] (2) mixing the first modified resin obtained in step (1) with an organic phosphonic acid to carry out a complex reaction to obtain a second modified resin;
[0040] (3) mixing the second modified resin obtained in step (2) with nano-alumina to obtain an impregnated material;
[0041] (4) The base paper is immersed in the impregnating material obtained in step (3), taken out, and cross-linked and cured to obtain wear-resistant melamine impregnated paper.
[0042] The present invention mixes imine with melamine urea-formaldehyde resin and performs Mannich reaction to obtain the first modified resin.
[0043] In the present invention, the imine and melamine urea formaldehyde resin are the same as the imine and melamine urea formaldehyde resin in the wear-resistant melamine impregnated paper described in the above technical solution, and will not be described in detail here.
[0044] In the present invention, the method of mixing the imine and the melamine urea-formaldehyde resin is preferably stirring. The present invention promotes the Mannich reaction between the imine and the melamine urea-formaldehyde resin by stirring. The present invention has no special limitation on the rotation speed of the stirring, which can be adjusted as needed.
[0045] In the present invention, the temperature of the Mannich reaction is preferably 25-30°C, more preferably 25°C; the time of the Mannich reaction is preferably 10-15 minutes, more preferably 10 minutes. The present invention controls the temperature and time of the Mannich reaction within the above range, which is more conducive to promoting the full reaction of the imine and the melamine urea-formaldehyde resin.
[0046] In the present invention, in the first modified resin, the mass ratio of diamine to melamine urea-formaldehyde resin is preferably (1-3): 110, more preferably 1: 110. The present invention controls the volume ratio of diamine to melamine urea-formaldehyde resin within the above range, so that diamine can be fully grafted onto melamine urea-formaldehyde resin.
[0047] After obtaining the first modified resin, the present invention mixes the first modified resin with an organic phosphonic acid to carry out a complex reaction to obtain a second modified resin.
[0048] In the present invention, the organic phosphonic acid is preferably an aqueous solution of organic phosphonic acid. In the present invention, the mass concentration of the aqueous solution of organic phosphonic acid is preferably 50-70wt%, more preferably 70wt%. In the present invention, adding the organic phosphonic acid in the form of an aqueous solution of organic phosphonic acid is more conducive to promoting a more uniform mixing of the first modified resin and the organic phosphonic acid and a more complete reaction.
[0049] The present invention has no particular limitation on the method for mixing the first modified resin and the organic phosphonic acid. A conventional mixing method can be used to mix the two uniformly. In the present invention, the method for mixing the first modified resin and the organic phosphonic acid is preferably stirring.
[0050] In the present invention, the temperature of the complexing reaction is preferably 25-30°C, more preferably 25°C; the time of the complexing reaction is preferably 30-35 minutes, more preferably 30 minutes. The present invention controls the temperature and time of the complexing reaction within the above range, which is more conducive to the full reaction of the first modified resin and the organic phosphonic acid.
[0051] In the present invention, the mass concentration of the organic phosphonic acid in the second modified resin is preferably 1.0-2.0 mg / mL, more preferably 2.0 mg / mL. The present invention limits the mass concentration of the organic phosphonic acid to the above range, which is more conducive to fully complexing nano-alumina and improving the dispersibility of nano-alumina.
[0052] After obtaining the second modified resin, the present invention mixes the second modified resin with nano-alumina to obtain an impregnated material.
[0053] In the present invention, the mass fraction of the nano-alumina in the second modified resin is preferably 1-3wt%, more preferably 3wt%. The present invention limits the mass fraction of the nano-alumina to the above range, which is more conducive to improving the wear resistance and strength of the impregnated paper.
[0054] The present invention has no special restrictions on the method of mixing the second modified resin with the nano-alumina, and a conventional mixing method can be used to mix the two uniformly. In the present invention, the method of mixing the second modified resin with the nano-alumina is preferably ultrasonic dispersion. The present invention has no special restrictions on the power and time of the ultrasound, and it can be adjusted according to the dispersion effect so that the nano-alumina can be fully dispersed in the second modified resin.
[0055] After obtaining the impregnating material, the present invention immerses the base paper in the impregnating material, takes it out, and crosslinks and solidifies it to obtain the wear-resistant melamine impregnated paper.
[0056] The present invention has no special limitation on the size of the base paper, and the base paper can be selected according to the required size. In an embodiment of the present invention, the length and width of the base paper are independently 15 cm.
[0057] In the present invention, the impregnation is preferably carried out at room temperature, and the impregnation time is preferably 1 to 2 minutes, more preferably 2 minutes. By immersing the base paper in the impregnation material for the above time range, the pores of the paper can be filled with the impregnation material.
[0058] In the present invention, the temperature of the cross-linking and curing is preferably 120-125°C, more preferably 120°C; the time of the cross-linking and curing is preferably 1-2 minutes, more preferably 2 minutes. The present invention can fully cross-link and cure the impregnated material impregnated on the paper to form a network structure within the above temperature and time range. The present invention has no special limitation on the cross-linking and curing device, and any conventional heating device can be used. In an embodiment of the present invention, the cross-linking and curing device is preferably a blast drying oven.
[0059] In the present invention, the synthesis mechanism diagram of the prepreg in the wear-resistant melamine impregnated paper is as follows: Figure 1 As shown. Figure 1 In the step (a), polyethyleneimine and melamine urea-formaldehyde resin are subjected to Mannich reaction to carry out polyethyleneimine grafting to obtain a first modified resin; step (b) is the polyethyleneimine of the first modified resin and phytic acid to obtain a second modified resin through a complex reaction; step (c) is the second modified resin and nano-alumina are mixed to obtain a prepreg. The method provided by the present invention is simple to operate, and a prepreg can be obtained. The prepreg is fully impregnated into base paper, and cross-linked and cured to form a three-dimensional network structure formed by cross-linking and curing melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-alumina.
[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] Example 1
[0062] A wear-resistant melamine impregnated paper, the wear-resistant melamine impregnated paper comprising base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing of melamine urea-formaldehyde resin, phytic acid, polyethyleneimine and nano-γ-alumina; wherein the mass ratio of melamine urea-formaldehyde resin, phytic acid, polyethyleneimine and nano-γ-alumina is 110:0.2:1:3.3;
[0063] The preparation method of the above-mentioned ground melamine impregnated paper is:
[0064] (1) stirring polyethyleneimine and melamine urea-formaldehyde resin at 25° C. for 10 minutes to perform a Mannich reaction to obtain a first modified resin; the mass ratio of polyethyleneimine to melamine urea-formaldehyde resin in the first modified resin is 1:110;
[0065] (2) the first modified resin obtained in step (1) is subjected to a complexation reaction with a 70 wt % phytic acid aqueous solution at 25° C. and stirred for 30 min to obtain a second modified resin; the mass concentration of phytic acid in the second modified resin is 2.0 mg / mL;
[0066] (3) ultrasonically mixing the second modified resin obtained in step (2) with nano-alumina (with a particle size of 10 to 20 nm) for 20 minutes to obtain an impregnation material; the mass fraction of the nano-alumina in the second modified resin in the impregnation material is 3 wt %;
[0067] (4) The base paper (15 cm×15 cm) was immersed in the impregnating material obtained in step (3) for 2 minutes, then taken out and placed in a forced air drying oven at 120° C. for 2 minutes for cross-linking and curing to obtain wear-resistant melamine impregnated paper.
[0068] Example 2
[0069] A wear-resistant melamine impregnated paper, comprising base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing melamine urea-formaldehyde resin, phytic acid, polyethyleneimine and nano-γ-alumina; wherein the mass ratio of melamine urea-formaldehyde resin, phytic acid, polyethyleneimine and nano-γ-alumina is 110:0.15:2:2.2;
[0070] The preparation method of the above-mentioned ground melamine impregnated paper is:
[0071] (1) stirring polyethyleneimine and melamine urea-formaldehyde resin at 25° C. for 10 minutes to perform a Mannich reaction to obtain a first modified resin; the mass ratio of polyethyleneimine to melamine urea-formaldehyde resin in the first modified resin is 2:110;
[0072] (2) the first modified resin obtained in step (1) is subjected to a complexation reaction with a 70 wt % phytic acid aqueous solution at 25° C. and stirred for 30 min to obtain a second modified resin; the mass concentration of phytic acid in the second modified resin is 1.5 mg / mL;
[0073] (3) ultrasonically mixing the second modified resin obtained in step (2) with nano-alumina (with a particle size of 10 to 20 nm) for 20 minutes to obtain an impregnation material; the mass fraction of the nano-alumina in the second modified resin in the impregnation material is 2 wt %;
[0074] (4) The base paper (15 cm×15 cm) was immersed in the impregnating material obtained in step (3) for 2 minutes, then taken out and placed in a forced air drying oven at 120° C. for 2 minutes for cross-linking and curing to obtain wear-resistant melamine impregnated paper.
[0075] Example 3
[0076] A wear-resistant melamine impregnated paper, comprising base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing melamine urea-formaldehyde resin, phytic acid, polyethyleneimine and nano-γ-alumina; wherein the mass ratio of melamine urea-formaldehyde resin, phytic acid, polyethyleneimine and nano-γ-alumina is 110:0.1:3:1.1;
[0077] The preparation method of the above-mentioned ground melamine impregnated paper is:
[0078] (1) stirring polyethyleneimine and melamine urea-formaldehyde resin at 25° C. for 10 minutes to perform a Mannich reaction to obtain a first modified resin; the mass ratio of polyethyleneimine to melamine urea-formaldehyde resin in the first modified resin is 3:100;
[0079] (2) the first modified resin obtained in step (1) is subjected to a complexation reaction with a 70 wt % phytic acid aqueous solution at 25° C. and stirred for 30 min to obtain a second modified resin; the mass concentration of phytic acid in the second modified resin is 1.0 mg / mL;
[0080] (3) ultrasonically mixing the second modified resin obtained in step (2) with nano-alumina (with a particle size of 10 to 20 nm) for 20 minutes to obtain an impregnation material; the mass fraction of the nano-alumina in the second modified resin in the impregnation material is 1 wt %;
[0081] (4) The base paper (15 cm×15 cm) was immersed in the impregnating material obtained in step (3) for 2 minutes, then taken out and placed in a forced air drying oven at 120° C. for 2 minutes for cross-linking and curing to obtain wear-resistant melamine impregnated paper.
[0082] Comparative Example 1
[0083] A method for preparing melamine impregnated paper is:
[0084] (1) stirring polyethyleneimine and melamine urea-formaldehyde resin at 25° C. for 10 minutes to perform a Mannich reaction to obtain a first modified resin; the mass ratio of polyethyleneimine to melamine urea-formaldehyde resin in the first modified resin is 1:110;
[0085] (2) the first modified resin obtained in step (1) is subjected to a complexation reaction with a 70 wt % phytic acid aqueous solution at 25° C. and stirred for 30 min to obtain a second modified resin; the mass concentration of phytic acid in the second modified resin is 2.0 mg / mL;
[0086] (3) The base paper (15 cm×15 cm) was immersed in the second modified resin obtained in step (2) for 2 min, then taken out and placed in a forced air drying oven at 120° C. for 2 min for cross-linking and curing to obtain melamine impregnated paper.
[0087] Comparative Example 2
[0088] A method for preparing melamine impregnated paper is:
[0089] (1) stirring polyethyleneimine and melamine urea-formaldehyde resin at 25° C. for 10 minutes to perform a Mannich reaction to obtain a first modified resin; the mass ratio of polyethyleneimine to melamine urea-formaldehyde resin in the first modified resin is 1:110;
[0090] (2) The base paper (15 cm×15 cm) was immersed in the first modified resin obtained in step (1) for 2 minutes, then taken out and placed in a forced air drying oven at 120° C. for 2 minutes for cross-linking and curing to obtain wear-resistant melamine impregnated paper.
[0091] Comparative Example 3
[0092] A method for preparing melamine impregnated paper comprises the following steps: cutting base paper into paper samples with a size of 15 cm×15 cm, impregnating the paper samples in melamine urea-formaldehyde resin for 2 minutes, and then taking the paper samples out and placing them in a forced air drying oven at 120° C. for 2 minutes.
[0093] Test Case
[0094] (1) In order to understand the reaction mechanism of modified MUF resin, the chemical structures of different modified resins were characterized by Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The FTIR images of MUF, MUF / PEI, MUF / PEI-PA and MUF / PEI-PA@Nano-Al2O3 are shown in Figure 2. Figure 2 As shown. Among them, MUF is melamine urea-formaldehyde resin, MUF / PEI is a polymer of melamine urea-formaldehyde resin and imine, MUF / PEI-PA is a polymer of melamine urea-formaldehyde resin, imine and polyamide, and MUF / PEI-PA@Nano-Al2O3 is a polymer of melamine urea-formaldehyde resin, polyethylene imine, polyamide and Al2O3. Figure 2 It can be seen that the peak found in the Fourier transform infrared spectrum of MUF resin is located at 3334 cm -1 、2952cm -1 、1566cm -1 and 1163cm -1 The 3334cm-1 peaks of MUF / PEI resin were respectively attributed to OH stretching vibration, CH symmetric stretching vibration in hydroxymethyl, NH bending vibration and COC symmetric stretching vibration. -1 and 1566cm -1 The relative peak intensity at 1566 cm / s increased. This increase in peak intensity is attributed to the grafting of polyethyleneimine (PEI) with the amino resin via the Mannich reaction. This reaction involves the amino groups of PEI with the active hydroxymethyl groups in the MUF resin, thereby increasing the number of NH groups. For the MUF / PEI-PA resin, the NH bending vibration of the primary amine in PEI increases from 1566 cm / s to 1566 cm / s. -1 Displaced to 1587cm -1 This shift is caused by the intermolecular hydrogen bonding between the P=O / PO groups in PA and the -NH2 groups in PEI. -1 The absorption peak detected at can be attributed to NH3 + (PO3) 2- The stretching vibrations of MUF / PEI-PA@Nano-Al2O3 resin at 3402 cm -1 and 746cm -1The peaks at 891 cm-1 are attributed to the stretching vibrations of OH and O-Al, which are characteristic vibrations of Nano-Al2O3. -1 The absorption peaks observed at 400 nm are attributed to the PO-Al bonds, which are formed by the interaction between PA and Al. 3+ The chelation between ions is formed because the phosphate groups in PA can easily chelate with a variety of metal ions through metal-organophosphate interactions.
[0095] To further verify the results, we recorded the XPS spectra of different modified resins such as Figure 3 As shown. Figure 3 It can be seen that the presence of C, N, P and O elements is clearly shown in the XPS full spectrum image of the MUF / PEI-PA@Nano-Al2O3 sample.
[0096] The high-resolution spectra of C1s, N 1s, P2p and O1s of MUF / PEI-PA@Nano-Al2O3 resin can fit multiple peaks, such as Figure 4 As shown. Figure 4 It can be seen that the peaks of the C 1s high-resolution spectrum are attributed to C=N (288.2 eV), CO / CN (286.1 eV) and CC (284.5 eV). The N 1s spectrum shows two peaks at 400.4 eV and 399.7 eV, corresponding to NH3 + In addition, the P 2p spectrum can be fitted with two peaks, located at 134.3 eV and 133.4 eV, corresponding to and HPO4 2- These observations further confirm the reaction mechanism of PEI and PA. The peaks in the O 1s high-resolution spectrum are attributed to P-OH (533.3 eV), POC / OC (532.5 eV), P=O (531.4 eV) and O-Al (531.1 eV). It is worth noting that PA and Al 3+ The coordination interaction between them leads to the appearance of O-Al peak, which is consistent with the FTIR results.
[0097] (2) Using a universal mechanical machine, tensile tests were performed on the impregnated papers prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively, and the results were shown in Table 1;
[0098] Using an oxygen index meter, flame retardancy tests were performed on the impregnated papers prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively. The results are shown in Table 1.
[0099] Table 1 Test results of impregnated papers prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0100] Tensile strength(MPa) Limiting oxygen index (%) Example 1 69.12 40.0 Example 2 61.16 40.0 Example 3 60.41 40.0 Comparative Example 1 61.2 40.0 Comparative Example 2 55.85 30.4 Comparative Example 3 28.12 30.2
[0101] As shown in Table 1, it can be seen from Example 1 and Comparative Example 1 that the tensile strength of the impregnated paper provided by the present invention is relatively high, which indicates that the present invention can improve the tensile strength of the impregnated paper by adding nano-alumina, so that it has good toughness. It can be seen from Example 1 and Comparative Examples 2 to 3 that the tensile strength of the impregnated paper provided by the present invention is relatively high, which indicates that the present invention effectively improves the toughness and flame retardancy of the impregnated paper by using polyethylene diamine and phytic acid.
[0102] (3) The impregnated papers provided in Examples 1 to 3 and Comparative Examples 1 to 3 were covered on the upper and lower surfaces of the blockboard and hot pressed to obtain an impregnated paper veneer blockboard. The hot pressing parameters were temperature 125° C., unit pressure 0.65 MPa, and time 7 min. The surface wear resistance of the impregnated paper veneer blockboard was tested using an abrasion tester, and the test results are shown in Table 2.
[0103] Table 2 Abrasion resistance test results of impregnated paper provided by Examples 1 to 3 and Comparative Examples 1 to 3
[0104]
[0105]
[0106] It can be seen from Table 2 that Examples 1 to 3 all exhibit excellent surface wear resistance compared to Comparative Examples 1 to 3, which indicates that nano-alumina plays a key role in improving the wear resistance of melamine impregnated paper.
[0107] It can be seen from the above results that the melamine impregnated paper provided by the present invention has excellent flame retardant properties and wear resistance. This is because the present invention grafts imine onto melamine urea-formaldehyde resin, and there are intermolecular hydrogen bonds and ion complexation between imine and organic phosphonic acid. The viscous coagulant generated by the reaction of the two effectively improves the toughness of the impregnated paper; since there are rich flame retardant nitrogen and phosphorus elements in the imine-phytic acid polyelectrolyte, it plays a positive role in the flame retardancy of the impregnated paper; in addition, there is a strong chelating effect between nano-alumina and organic phosphonic acid molecules, and it is uniformly dispersed in the melamine urea-formaldehyde resin, thereby improving the toughness and wear resistance of the impregnated paper.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A wear-resistant melamine impregnated paper, comprising base paper and a resin film impregnated on the base paper; the resin film is a three-dimensional network structure formed by cross-linking and curing of melamine urea-formaldehyde resin, organic phosphonic acid, imine and nano-aluminum oxide.
2. The wear-resistant melamine impregnated paper according to claim 1, characterized in that: The organic phosphonic acid includes one or more of phytic acid, citric acid and tannic acid.
3. The wear-resistant melamine impregnated paper according to claim 1, characterized in that: The imine includes one or more of polyethyleneimine, polydiethylenetriamine and chitosan.
4. The wear-resistant melamine impregnated paper according to claim 1, characterized in that: The nano-alumina includes one or more of α-alumina, β-alumina and γ-alumina.
5. The wear-resistant melamine impregnated paper according to claim 1, characterized in that: The mass ratio of the melamine urea-formaldehyde resin, organic phosphonic acid, imine and aluminum oxide is 110:(0.1-0.2):(1-3):(1.1-3.3).
6. The method for preparing the wear-resistant melamine impregnated paper according to any one of claims 1 to 5, comprising the following steps: (1) mixing imine with melamine urea-formaldehyde resin and performing Mannich reaction to obtain a first modified resin; (2) mixing the first modified resin obtained in step (1) with an organic phosphonic acid to carry out a complex reaction to obtain a second modified resin; (3) mixing the second modified resin obtained in step (2) with nano-alumina to obtain an impregnated material; (4) The base paper is immersed in the impregnating material obtained in step (3), taken out, and cross-linked and cured to obtain wear-resistant melamine impregnated paper.
7. The preparation method according to claim 6, characterized in that: The temperature of the Mannich reaction in step (1) is 25-30° C., and the time of the Mannich reaction is 10-15 min.
8. The preparation method according to claim 6, characterized in that: The temperature of the complexation reaction in step (2) is 25-30° C., and the time of the complexation reaction is 30-35 min.
9. The preparation method according to claim 6, characterized in that: The immersion time in step (4) is 1 to 2 minutes.
10. The preparation method according to claim 6, characterized in that: The temperature of cross-linking and curing in step (4) is 120-125° C., and the time of cross-linking and curing is 1-2 minutes.
Citation Information
Patent Citations
Flame-retardant impregnated paper and preparation method thereof
CN113026413A
